Prolonged use of statins and peripheral neuropathy: A systematic review (Annals of Medical Research, 2021)
Peripheral neuropathy is one of the most common neurological disorder. Traditionally, diabetes mellitus is the most common aetiology of peripheral neuropathy. However, there are many other aetiologies of peripheral neuropathy, such as drug-induced, spinal trauma, alcoholism, vitamin B12 deficiency, and many more. In previous studies, long-term statin use was also associated with peripheral neuropathy.We conducted a systematic search through PubMed and Embase using the protocol following the PRISMA statement in making a systematic review. W e included article that published in the last 10 years (from 2011 until July 2020). Two reviewers extracted data from the articles that have been selected. We extracted the study population, study design, type of intervention, control variable, p-value, and the outcome of the study We found 250 journals in our search strategy, and at the end, 4 journals included. Some studies revealed that peripheral neuropathy  was observed during the long-term treatment of statin. However, some studies also revealed that statin does not increase the risk of peripheral neuropathy.The possible mechanism of statin-induced peripheral neuropathy in humans are disturbing the function and integrity of cell membrane, the role of alfa-tocopherol or Vitamin E, and the role of ubiquinone (Coenzyme Q10). In contrast, it is believed that statins lowering the risk of peripheral neuropathy through the anti-inflammatory effects of statins. Different result from each study can be caused by various factors. Besides the peripheral neuropathy side effect that described in the literature, statins are well tolerated. Awareness the side effects would lead to better treatment. Future study about association between statins and peripheral neuropathy is needed.